Bahasa Melayu Stemmer / Subbu Valliappan - Subbu , Valliappan (2004)
This report introduces the project, titled Bahasa Melayu Stemmer, and provides a detailed description of system.There are a total of four chapters in this report, and all the chapters are dedicated entirely to the stemmer project. Each of the chapter presents an explanation of the system in a different perspective as to enhance one's understanding of this stemmer.The main idea of this project is to build stemmer that can stem any given words, and to develop a standard stemming algorithm in Malay Language. The language Malay is particularly chosen because there is a lack pf complete stemmers that exist for this language at the moment. Another objective of this system implementation is to study more about the stemmer architecture. Unlike other stemmers, this stemmer would not use complex and difficult artificial intelligence techniques such as complicated knowledge representation and major parsing. This Stemmer has a wide variety of applications and it caters for a vast age group. It is expected that when this system is developed and fully utilized, it will benefit its users and customers tremendously withh all of its powerful features. I truly hope that this report, and the stemmer system as well, will open up the eyes of researchers and bring a new dimension to the worlf of stemming.